Hippeastrum euryphyllum (Amaryllidaceae), a microendemic species from northeastern Argentina: new combination, description, taxonomic identity and distribution - Florentín, Javier E.; Medina, Walter A.; Salas, Roberto M.; Roitman, German (Phytotaxa, 2023)
As part of a series of taxonomic and floristic studies of the endemic vascular flora from Corrientes-Argentina, here we focus our attention on the genus Hippeastrum (Amaryllidaceae). Two species Hippeastrum angustifolium Pax, and Hippeastrum striatum (Lam.) H.E. Moore are cited for Corrientes, Argentina. However, another related taxon, Amaryllis euryphylla Ravenna, a microendemic species from Paraje Tres Cerros, is also recognized for the province. After a detailed study of all original available material, numerous herbarium specimens, and new field collections, we perform a new combination of Amaryllis euryphylla under the genus Hippeastrum as H. euryphyllum. In addition, photographs in its habitat, comments on the geographic distribution and identification key for Hippeastrum species from Corrientes are provided.